Ottoman-French rapprochement (1520-1566 AD) (A historical study) (Latakia University (formerly Tishreen) Journal for Research and Scientific Studies - Arts Humanities Series, 2026)
The fifteenth century witnessed the beginnings of Franco-Ottoman relations, which initially revolved around hostility and war against the Turkish element that was sweeping through the Balkans and the Mediterranean at that time. These relations began with Sultan Bayezid II's attempt to negotiate with the French King Louis XI during the conflict between him and his brother Cem. However, these relations and attempts at rapprochement failed. Thus, it can be said that the origins of the relationship between France and the Ottoman state are old, and these relations moved to a stage of actual alliance during the tenth century AH/sixteenth century AD amidst the internal European conflicts of that century. France looked to the Ottoman state as a friend and trusted ally, which was at the height of its glory and power. This rapprochement was reflected positively on the French side, as it obtained special privileges that other European countries did not have through the Treaty of Capitulations (948 AH/1535 AD), which granted France special advantages and laid the foundations for political, economic, and military cooperation between the two states. It also gave France the right to intervene in the Ottoman provinces under the pretext of protecting its subjects. Consequently, relations between the Ottoman and French sides varied, sometimes characterized by cordiality and rapprochement, and at other times by tension and contradiction, ever since the signing of that treaty.
Keywords: France – Ottoman Empire – rapprochement – treaty – privileges